(untitled) (Global Journal of Management and Business Research, 2019)
China is the world’s largest producer of photovoltaic -PV power with total installed solar capacity surpassing the early leaders in solar energy developed countries viz;USA, Germany, Japan,Italy,France, and UK.The electricity consumption of China exceeds that of any other nation and China is also the top-most solar producerwith fast-growing PV systems. This paper focuses on Residential SolarPVand the progress made by China-its evolution of solar policies, trends, challenges overcome, progress made and the future of sustainable solar energy development envisaged by China. A comparison of the trajectory of growth in Residential Solar PVs in India is made to analyze the concrete government policies in this segment and the consistency and growth of RSTPV in India. The challenges faced by India and the reasons for slow growth in this sector are explored. The time is now ripe for India to focus on the RSTPV segment while implementing the Jawaharlal Nehru National Solar Mission(JNNSM) and learning lessons from China’s experiences to become a global PV leader in harnessing solar energy.